Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.21037/jtd-20-2651
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding is the most common cause of unplanned return to operating room after lung cancer surgeries

Abstract: Background: The rate of unplanned return to the operation room (UROR) is an important index for the quality of surgeries. Study of the features and causes of patients who have suffered UROR is key to reduce the risk of it. Methods: A retrospective, observational study was conducted among lung cancer patients who have received lung resections and UROR over a 5-year period. The causes, findings, procedures of UROR and recovery of patients were examined. Results: Among the 23,345 lung cancer surgeries, 64 underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
5
1
Order By: Relevance
“…The incidence of unplanned reoperation is 0.53% in our study, which is higher than the published 0.27% (after lung cancer surgeries) [8], probably due to the included benign tumors herein. Indeed, the benign tumors were reported to be more risky to postoperative bleedings than the malignant tumor, potentially due to inflammation [11].…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…The incidence of unplanned reoperation is 0.53% in our study, which is higher than the published 0.27% (after lung cancer surgeries) [8], probably due to the included benign tumors herein. Indeed, the benign tumors were reported to be more risky to postoperative bleedings than the malignant tumor, potentially due to inflammation [11].…”
Section: Discussioncontrasting
confidence: 79%
“…Therefore, pulmonary parenchyma should be evaluated prior to the selection of a suitable and matched staple cartridge. Interestingly, one-third of these 31 hemothorax (10 cases) including 5 clotted hemothorax and 5 active hemorrhages, had no definite bleeding sites, accordant to the reported incidence (37.7–41%) [ 8 , 9 ], which can be attributed to chest wall vessels and may be ignored during reoperation via the initial incision [ 10 ]. Furthermore, our study indicated pleural adhesion is also a risk factor for the bleedings from the chest wall and pleural, especially in some “blind” areas, e.g., vicinity of incision and costophrenic angle.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A plausible explanation for the recorded differences in the estimated blood loss between RATS and VATS may lie in the technical advantages provided by the robotic platform. The three-dimensional, magnified field of view, the elimination of tremor, and the more flexible equipment offered by RATS can allow surgeons to better identify anatomical relationships and control bleeding that occurs during the dissection of hilar and mediastinal lymph nodes, which represents an important source of blood loss during lung cancer surgery [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of unplanned reoperation after lung surgery ranges from 1.01% to 1.09% [ 2 , 5 ], while it varies between 0.27% and 1.76% in lung cancer surgery [ [6] , [7] , [8] ]. One study reported a decreasing trend of reoperation rate over time [ 8 ].…”
Section: Introductionmentioning
confidence: 99%